Comparison of the seventh and eighth edition american joint committee on cancer oral cavity staging systems. (15th April 2018) - Cramer, John D.; Reddy, Abhita; Ferris, Robert L.; Duvvuri, Umamaheswar; Samant, Sandeep
Abstract : Objective: For the first time in 30 years, the eighth edition of the American Joint Committee on Cancer (AJCC) Staging Manual offers major changes in the staging of oral cavity cancer. We evaluated the predictive ability of the new staging system for oral cavity cancer to validate these changes and hypothesized that the new system would improve prognostic accuracy. Methods: We conducted a retrospective cohort study of patients with oral cavity squamous cell carcinoma in the National Cancer Data Base from 2009 to 2013 and applied the seventh and eighth edition staging AJCC staging systems to all patients. Stage‐specific overall survival was calculated using the Kaplan‐Meier method and concordance indices to measure the system's prognostic accuracy. Results: We identified 39, 361 patients with a median follow‐up of 27.1 months (range 0.1–80.4 months). In the seventh edition, there were 43.0%, 15.0%, 10.6%, and 25.7% of patients with pathologic stage I, II, III, and IV disease, respectively. After restaging based on eighth edition pathological guidelines, 10.0% of patients were upstaged (38.1%, 18.1%, 14.2%, and 25.2%, respectively, with stage I, II, III, and IV disease, respectively). The survival concordance index improved from the seventh to eighth edition for pathological staging (concordance index 0.699 and 0.704, respectively) and for clinical staging (concordance index 0.714 and 0.715, respectively). Conclusion: We provide validation of the new AJCC staging system for oral cavity cancer. Eighth edition AJCC staging guidelines upstage a substantial number of patients with greater depth of invasion or extranodal extension. This resulted in slightly improved prognostication. Level of Evidence: 2c. Laryngoscope, 128:2351–2360, 2018